IDENTIFIKASI VARIABEL SISTEM INSENTIF DALAM PROYEK KERJASAMA PEMERINTAH SWASTA (KPS) JALAN TOL - Putu Ika Wahyuni; Sarwono Hardjomuljadi; Hendrik Sulistio; K. Koespiadi (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2018)
Gaps Infrastructure financing in Indonesia must be sought out, one of which is to improve the performance of PPP projects to be bankable / economically viable / investment-worthy so that investors / private companies are willing / interested in investing in infrastructure projects. with Malaysia which now has more than 3000 km of toll roads. The incentive system is implemented in developed countries to improve the performance of feasibility and anticipate risks in toll road KPS projects that have long-term contract / concession time. Burris, Baker, Geiselbrecht (2014). The government needs to make a breakthrough to provide space utilization incentives as a form of controlling the use of space where investors and the public can participate by working together to increase toll revenues. The intended use of space is the management of the area around the toll road with a certain amount of area and the allocation of the management plan that has the maximum economic impact so that investors can obtain other income that can be included in the toll revenue cash flow. This study uses the AHP method with digital analysis with Expert Choice to produce the following analysis: the highest criteria for incentive for space utilization activities. The highest sub-criteria are in the physical provision of compensation from the government to the community where the land is applied to incentives for spatial use.